Low-power and high-detectivity Ge photodiodes by in-situ heavy As doping during Ge-on-Si seed layer growth - Lin, Yiding (2021)
Germanium (Ge)-based photodetectors have become one of the mainstream components in photonic-integrated circuits (PICs). Many emerging PIC applications require the photodetectors to have high detectivity and low power consumption. Herein, we demonstrate high-detectivity Ge vertical p-i-n photodiodes on an in-situ heavily arsenic (As)-doped Ge-on-Si platform. The As doping was incorporated during the initial Ge-on-Si seed layer growth. The grown film exhibits an insignificant up-diffusion of the As dopants. The design results in a ∼45× reduction on the dark current and consequently a ∼5× enhancement on the specific detectivity (D*) at low reverse bias. The improvements are mainly attributed to the improved epi-Ge crystal quality and the narrowing of the device junction depletion width. Furthermore, a significant deviation on the AsH3 flow finds a negligible effect on the D* enhancement. This unconventional but low-cost approach provides an alternative solution for future high-detectivity and low-power photodiodes in PICs. This method can be extended to the use of other n-type dopants (e.g., phosphorus (P) and antimony (Sb)) as well as to the design of other types of photodiodes (e.g., waveguide-integrated).